Study of Kridosono’s Urban Quality Space in Yogyakarta using TUSA - Wiliarto Wirasmoyo; Desrina Ratriningsih (Departement of Architecture, Universitas Islam Indonesia, 2023)
The importance of public spaces is one of United Nations’ Goals. Green Open Space in Kridosono which is aspired by the government is a public open space that can be easily accessed by the public and as main open space contributes as a sports field. Based on other studies related to Kridosono, most of them questioned how to improve the urban space quality of the Kridosono area as a public open space. This study aims to examine the elements that are factors in improving the urban space quality, so that we can know and feel of optimal spatial quality as a Public Open Space. Tools for Urban Space Analysis (TUSA) is a novelty/state of the art/novelty in the discussion. The results are to obtain elements related to improve the urban space quality, to fulfill all Nodal, Spatial and Environmental attributes and values for Hardware & Use-Socio Perception for Software. Keywords: Kridosono; Open Space; TUSA; Urban Space Quality